2021
DOI: 10.9734/ijbcrr/2021/v30i130247
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Effect of Thermal Treatments on the Enzymatic Browning Inhibition of Violet Eggplant (Solanum melongena L.) Cultivated in Daloa (Côte d’Ivoire)

Abstract: Background: The polyphenol oxidase (PPO) responsible for the enzymatic browning of fruits and vegetables, has been involved in the undesirable brown discolouration of food products that resulted in negative effects on colour, taste, and nutritional value. This is a generally undesired process and needs to be prevented in food technology. Objective: The present work was carried out to evaluate the effect of chemical and thermal treatments on browning inhibition of eggplant fruit (Solanum melongena L.).&#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Based on this experiment, heat treatment with an intermediate temperature and time ratio of 50 °C and 60 s respectively was selected as the best combination to maintain visual quality and reduce the browning of fresh-cut eggplants for 8 days. This agrees with what was reported by Constant et al (2021), who reported that heat treatment at 65 °C for 30 min considerably reduced browning by inhibiting PPO activity, as well as the use of the antioxidant ascorbic acid, reducing this enzyme by approximately 80% in whole eggplants. In this way, Loaiza-Velarde et al ( 2003) also discovered that applying heat shock at 50 °C for 90 s delayed the browning potential increase in fresh-cut celery petioles by three weeks.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…Based on this experiment, heat treatment with an intermediate temperature and time ratio of 50 °C and 60 s respectively was selected as the best combination to maintain visual quality and reduce the browning of fresh-cut eggplants for 8 days. This agrees with what was reported by Constant et al (2021), who reported that heat treatment at 65 °C for 30 min considerably reduced browning by inhibiting PPO activity, as well as the use of the antioxidant ascorbic acid, reducing this enzyme by approximately 80% in whole eggplants. In this way, Loaiza-Velarde et al ( 2003) also discovered that applying heat shock at 50 °C for 90 s delayed the browning potential increase in fresh-cut celery petioles by three weeks.…”
Section: Sensory Evaluationsupporting
confidence: 93%